PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN AKUNTANSI SUMBER DAYA MANUSIA - Andarista Puji Rahayu; Ardiani Ika Sulistyawati (Solusi, 2019)
ABSTRACT Human resources is an intangible asset and is the most important factorthat determines the success of the company . The role of human resources (HR) inthe development of the business world that is increasingly rapidly considered veryimportant for any company . Qualified human resources will lead theorganization in both comparative advantage and competitive basis and wasinstrumental in running the company's operations and optimally executingbusiness strategy .This research aims to determine the effect of company size , sizeof board of commissioners , the concentration of ownership and status on thedisclosure of accounting lisitng human resources . Type of data used in this study is secondary data. Purposive samplingmethod used in sample selection. The results of this study prove thatsimultaneously (F est) accounting disclosure index of human resources can beexplained by all the variables. While (t test) indicates that the variable board sizesignificantly influence accounting disclosure of human resources . Keywords :human resources accounting disclosure, company size, theconcentration of ownership and listing status